Karakteristik Fisik dan Potensi Ampas Tahu sebagai Bahan Pakan Alternatif dari Sentra Produksi Tahu di Desa Gadingrejo Induk, Kabupaten Pringsewu - anggi derma tungga dewi; Ririn Angriani (AVES: Jurnal Ilmu Peternakan, 2025)
This study aimed to evaluate the physical characteristics and pH of tofu pulp from various production sites in Gadingrejo Induk Village, Gadingrejo Sub-district, Pringsewu Regency, Lampung Province, as an alternative feed ingredient for livestock. A total of 14 tofu by-product samples were collected from local production units and analyzed using organoleptic methods for five physical parameters: color, aroma, texture, cleanliness, and homogeneity. In addition, pH measurements were conducted to assess the freshness and potential fermentation of the material. The results showed significant variation in quality among samples. Samples S3 and S10 exhibited the best characteristics, including bright color, neutral aroma, smooth texture, high cleanliness and homogeneity, and near-neutral pH values (7.03–7.40). In contrast, sample S4 had the lowest scores in most parameters, including a low pH (5.13), indicating spontaneous fermentation. There were clear correlations between pH and both aroma and cleanliness, as well as between texture and homogeneity. In conclusion, tofu by-products from production centers with good sanitation and proper processing have high potential to be utilized as safe and viable livestock feed ingredients.